Determinant of Abdominal Wound Dehiscence (AWD) in Post-Laparotomy Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Dwirian Putra, M. Arisma; Efman EU Manawan; Mgs. Irsan Saleh (Sriwijaya Journal of Surgery, 2023)
Introduction. Abdominal wound dehiscence (AWD) is a significant risk factor for mortality during the perioperative period. The high mortality rate, prolonged hospitalization, and increased incidence of repeat operations increase in hospital costs result in worsening the AWD problem itself. This study aims to determine the determinants of abdominal wound dehiscence in post-laparotomy patients at the Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods. This study is quantitative analytical research with a cross-sectional design to determine the determinants of abdominal wound dehiscence (AWD) in post-laparotomy patients based on secondary data from medical records at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. A total of 161 research subjects participated in this study. Results. Emergency surgery patients are 0.4 times more likely to experience AWD than elective patients. Then, patients who experience hypoalbuminemia have 1.8 times the risk, those aged more than 60 years have 0.5 times the risk, sepsis has 1.5 times the risk, and trauma patients have 0.8 times the risk of experiencing AWD. Conclusion. Emergency surgery is the most influential determinant in the incidence of AWD at Dr. Mohammad Hoesin Palembang, Indonesia.